Ekosistem Perairan Payau Di Pantai Charlita Desa Afia, Gunungsitoli Utara - Gulo, Florencelin Dwinda (Jurnal Perikanan dan Kelautan, 2025)
The brackish water ecosystem is a transitional zone between freshwater and seawater, rich in biodiversity and possessing vital ecological functions. This study was conducted at Charlita Beach, North Gunungsitoli, using field observation methods with a qualitative approach. The results revealed the presence of Rhizophora mucronata mangroves, characteristic fauna such as silverside fish, mangrove crabs, and sea snails, as well as abiotic conditions including calm salty water and muddy substrates. Local tourism activities provide positive economic impacts but require proper management to avoid damaging the ecosystem. This study emphasizes the importance of protecting and sustainably managing brackish water ecosystems.